Graphene@Ni0.5Co0.5Fe2O4 hybrid framework with enhanced interfacial polarization for electromagnetic wave absorption - Wahaab, F.A. (Elsevier Ltd, 2021)
Fabrication of smart materials for electromagnetic (EM) wave absorption has been propounded as efficient EM interference and pollution mitigation method. Herein, a porous lightweight graphene@Ni0.5Co0.5Fe2O4 composite was prepared via a coprecipitation method. The results show that Ni0.5Co0.5Fe2O4 nanoparticles are homogeneously dispersed and anchored on the graphene flakes. Investigation of the EM waves absorption properties of the material at different filling in paraffin reveals that at 15 wt loading, the composite absorbs large percent of the EM waves at minimal thickness. The composite attains optimum reflection loss peak â44.7 dB at 17.45 GHz, with 1.5 mm thickness. This enhanced EM wave absorption performance (at lesser thickness than Ni0.5Co0.5Fe2O4 in literature) could be ascribed to interfacial polarization and a good impedance match arising from unique pore configuration of the dielectric (graphene) and magnetic (Ni0.5Co0.5Fe2O4) composite. These results indicate that the lightweight G@Ni0.5Co0.5Fe2O4 composites with strong absorption at reduced thickness is an efficient absorber for high-frequency EM wave attenuation. Â© 2020 Elsevier B.V.